2022
DOI: 10.3389/fgene.2022.844800
|View full text |Cite
|
Sign up to set email alerts
|

TP53 /KRAS Co-Mutations Create Divergent Prognosis Signatures in Intrahepatic Cholangiocarcinoma

Abstract: Background: Due to high invasiveness and heterogeneity, the morbidity and mortality of intrahepatic cholangiocarcinoma (ICC) remain unsatisfied. Recently, the exploration of genomic variants has decoded the underlying mechanisms of initiation and progression for multiple tumors, while has not been fully investigated in ICC.Methods: We comprehensively analyzed 899 clinical and somatic mutation data of ICC patients from three large-scale cohorts. Based on the mutation landscape, we identified the common high-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…After study selection, 77 studies [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ,…”
Section: Resultsunclassified
See 2 more Smart Citations
“…After study selection, 77 studies [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ,…”
Section: Resultsunclassified
“…The most prevalent mutations were in TP53 (42.7%), ARID1A (21.7%), KRAS (15.7%), IDH1 (8.7%), CDKN2A (7.8%), BAP1 (6.7%), suppressor of others against decapentaplegic ( SMAD4 ) (6.5%), and PIK3CA (6.0%). Guo et al [ 19 ] investigated 899 patients with ICC and found that TP53 (18–40%) and KRAS (10–18%) were high-frequency mutation genes. Other mutations were found in ARID1A , SMAD4 , spectrin repeat-containing nuclear envelope protein 1 ( SYNE1 ), mucin 16 ( MUC16 ), BAP1 , LDL receptor-related protein 1B ( LRP1B ), fibrous sheath-interacting protein 2 ( FSIP2 ), ephrin type-A receptor 2 ( EPHA2 ), IDH1 , IDH2 , polybromo 1 ( PBRM1 ), v-raf murine sarcoma viral oncogene homolog B1 ( BRAF ), ATM , FGFR2 , C16orf3 , human leukocyte antigen A ( HLA-A ), HLA-C , titin gene ( TTN ), family with sequence similarity 230 member A ( FAM230A ), AHNAK2 , and CTD-3193O13.9.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relevant cooperation of TP53 and KRAS in promoting the development and the malignancy of iCCA is directly supported by a recent study reporting a molecular and clinicopathologic analysis on 3 large cohorts of iCCA patients extensively characterized at molecular and clinical levels: TP53 and KRAS mutations were associated with a poor prognosis and this phenomenon was particularly evident for double mutant ( TP53/KRAS ) patients. 70…”
Section: Cellular Origin Of Biliary Cancersmentioning
confidence: 99%
“…The relevant cooperation of TP53 and KRAS in promoting the development and the malignancy of iCCA is directly supported by a recent study reporting a molecular and clinicopathologic analysis on 3 large cohorts of iCCA patients extensively characterized at molecular and clinical levels: TP53 and KRAS mutations were associated with a poor prognosis and this phenomenon was particularly evident for double mutant (TP53/ KRAS) patients. 70 Guest et al 71 reported the development of an iCCA model based on chronic liver inflammation and transfection with mutant TP53 leads to the development of iCCA generated from cholangiocytes: in these tumors, the induction of NOTCH3 is required for oncogenic transformation of cholangiocytes. Interestingly, NOTCH3 was found to be the NOTCH family receptor mostly overexpressed in human iCCAs.…”
Section: Cellular Origin Of Biliary Cancersmentioning
confidence: 99%